FACTORS ASSOCIATED WITH MASK USE BEHAVIOR AMONG WORKERS OF THE KATARAJA TOLL ROAD CONSTRUCTION PROJECT IN 2024 - Handayani, Puji; Iriani, Dewi Utami (Universitas Brawijaya, 2024)
In toll road construction projects, some jobs cause high levels of Particulate Matter, such as breaking, road cleaning, and others. Thus, workers must use masks, such as KN95, KF94, or N95 masks. According to the Health Belief Model (HBM) theory, mask-use behavior is influenced by perceived threat, perceived benefits, perceived barriers, self-efficacy, cues to action, and sociodemographics. This study aims to determine the factors associated with mask-use behavior among workers of the Kataraja section 1 toll road construction project in 2024. The study design used was cross-sectional with a sample size of 70 workers taken by purposive sampling. Data collection was carried out using a questionnaire with interview techniques. The data obtained were analyzed using univariate and bivariate analysis with the Chi-Square test. The results showed that 44.3% of workers had poor mask use behavior, such as not washing hands before using a mask, not changing masks regularly, and not disposing of mask waste in its place. There is a significant relationship between education level (OR=81), knowledge level (OR=11), perceived threat (OR=8.31), perceived benefits (OR=59.06), perceived barriers (OR=7.32), self-efficacy (OR=38.85), and the role of supervisors (OR=10.17) with mask use behavior. To improve poor behavior in workers, companies need to provide informal education regarding the dangers of Particulate Matter and the benefits and procedures for using masks. In addition, workers still find it difficult to change masks, so companies should pay attention tothe quality and quantity of masks and make it easier for workers to take them.